Aceh Barat Daya مشكلات الطالبات على ترجمة كتب التراث بمعهد جبل النور الجديد - Idris, Aisyah; Badruzzaman, Badruzzaman; Fithriani, Ulva (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
Some students at the jabal nur jadid islamic boarding school had difficulty translating the Kuthubu At-Thuras. Therefore, the purpose of this study is to find out what problems are faced by the students of the Jabal Nur Jadid islamic boarding school in translating the Kuthubu At-Thuras and what efforts are made by the teachers to overcome these difficulties. The method used by researchers in this study is descriptive method, where researchers conduct interviews to obtain the required data. And the sample in this study were 20 students. The results of this study are problems when translating the Kuthubu At-Thuras, especially in terms of language problems, namely in terms of vocabulary,grammer,language preparation, literacy and language development. The teacher’s efforts in overcoming their problems were the teacher telling the students to memorize the lessons (vocabulary and grammer) and over and over again, asking the tudesnts to practice translating arabic texts, making concept maps to teach grammer, outside of class haurs to teach studest grammer and the teacher used vocabulary thant was easily understood by the students when translating the Kuthubu At-Thuras.